Experimental study on the corrosion durability of cracked high performance fiber reinforced cementitious composites - Ahmed, Shaikh; Mihashi, H.; Mizukami, T.; Shimozawa, K.; Nagayama, M. (Asian concrete federation, 2006)
This paper presents some experimental results on the corrosion durability of reinforced concrete (RC) beams made with ordinary mortar and fiber reinforced cementitious composites (FRCC) containing mono and hybrid fibers. Corrosion durability of cracked RC beams with three different crack widths (i.e. 0.3mm, 0.4mm and 0.5mm) are also evaluated here. All cracked and uncracked beams are subjected to cyclic wetting and drying using water containing 3% NaCl. In additon, an external potential is also applied across the anode and the cathode to accelerate the corrosion. Corrosion of steel bars is monitored through a pair of sensors attached to the reinforcing bars in each beam. Test results show that both mono and hybrid fiber FRCC exhibited better corrosion protection than that of ordinary mortar. In case of cracked RC beams, as expected, the beams with smaller crack widths exhibited lower level of corrosion than that of larger crack widths.